Slovensko-nemška medkulturnost v literarnem delu Petra Handkeja - Borovnik, Silvija (Jezik in slovstvo, 2014)
Peter Handke (1942), a writer born to a Slovenian mother in the village of Griffen in Austrian Carinthia, is one of the key names of contemporary Austrian and German literature. In many of his works, Slovenian elements can be identified at the levels of theme, motif and language. On the basis of these elements, the author can be considered a typical representative of German-Slovenian intercultural identities, as is demonstrated in the article by way of an analysis of two of Handke%s works, the novel Repetition (Wiederholung) and the novel-drama Storm Still (Immer noch Sturm). Both works also thematise the history of Carinthian Slovenes, especially the German-Slovenian relationship in Austria.
Keywords: Handke, Peter, 1942-; slovensko-nemška medkulturnost; slovenščina; Slovene; identiteta